Whole-genome analysis of histone H3 lysine 27 trimethylation in Arabidopsis. - Xiaoyu Zhang; Oliver Clarenz; Shawn Cokus; Yana V Bernatavichute; Matteo Pellegrini; Justin Goodrich; Steven E Jacobsen (PLoS Biology)
Trimethylation of histone H3 lysine 27 (H3K27me3) plays critical roles in regulating animal development, and in several cases, H3K27me3 is also required for the proper expression of developmentally important genes in plants. However, the extent to which H3K27me3 regulates plant genes on a genome-wide scale remains unknown. In addition, it is not clear whether the establishment and spreading of H3K27me3 occur through the same mechanisms in plants and animals. We identified regions containing H3K27me3 in the genome of the flowering plant Arabidopsis thaliana using a high-density whole-genome tiling microarray. The results suggest that H3K27me3 is a major silencing mechanism in plants that regulates an unexpectedly large number of genes in Arabidopsis (~4,400), and that the maintenance of H3K27me3 is largely independent of other epigenetic pathways, such as DNA methylation or RNA interference. Unlike in animals, where H3K27m3 occupies large genomic regions, in Arabidopsis, we found that H3K27m3 domains were largely restricted to the transcribed regions of single genes. Furthermore, unlike in animals systems, H3K27m3 domains were not preferentially associated with low-nucleosome density regions. The results suggest that different mechanisms may underlie the establishment and spreading of H3K27me3 in plants and animals.